A gain‐of‐function mutation in the ITPR1 gating domain causes male infertility in mice. Issue 8 (27th May 2022) - Sun, Bo; Ni, Mingke; Tian, Shanshan; Guo, Wenting; Cai, Shitian; Sondergaard, Mads T.; Chen, Yongxiang; Mu, Yongxin; Estillore, John P.; Wang, Ruiwu; Chen, Ju; Overgaard, Michael T.; et al.
Abstract: Inositol 1, 4, 5‐trisphosphate receptor 1 (ITPR1) is an intracellular Ca 2+ release channel critical for numerous cellular processes. Despite its ubiquitous physiological significance, ITPR1 mutations have thus far been linked to primarily movement disorders. Surprisingly, most disease‐associated ITPR1 mutations generate a loss of function. This leaves our understanding of ITPR1‐associated pathology oddly one‐sided, as little is known about the pathological consequences of ITPR1 gain of function (GOF). To this end, we generated an ITPR1 gating domain mutation (D2594K) that substantially enhanced the inositol trisphosphate (IP3 )‐sensitivity of ITPR1, and a mouse model expressing this ITPR1‐D2594K +/ − GOF mutation. We found that heterozygous ITPR1‐D2594K +/ − mutant mice exhibited male infertility, azoospermia, and acrosome loss. Furthermore, we functionally characterized a human ITPR1 variant V494I identified in the UK Biobank database as potentially associated with disorders of the testis. We found that the ITPR1‐V494I variant significantly enhanced IP3 ‐induced Ca 2+ release in HEK293 cells. Thus, ITPR1 hyperactivity may increase the risk of testicular dysfunction. Abstract : The inositol 1, 4, 5‐trisphosphate receptor 1 (ITPR1) mutation enhanced inositol trisphosphate (IP3 )‐induced fractional Ca2+ release and is potentially linked to male Infertility.